Enhanced fuzzy logic‐based spray and wait routing protocol for delay tolerant networks. (29th May 2014) - Jain, Sweta; Chawla, Meenu; Soares, Vasco N. G. J.; Rodrigues, Joel J.
Summary: Delay tolerant networks are a class of ad hoc networks that enable data delivery even in the absence of end‐to‐end connectivity between nodes, which is the basic assumption for routing in ad hoc networks. Nodes in these networks work on store‐carry and forward paradigm. In addition, such networks make use of message replication as a strategy to increase the possibility of messages reaching their destination. As contact opportunities are usually of short duration, it is important to prioritize scheduling of messages. Message replication may also lead to buffer congestion. Hence, buffer management is an important issue that greatly affects the performance of routing protocols in delay tolerant networks. In this paper, Spray and Wait routing protocol, which is a popular controlled replication‐based protocol for delay tolerant networks, has been enhanced using a new fuzzy‐based buffer management strategy Enhanced Fuzzy Spray and Wait Routing, with the aim to achieve increased delivery ratio and reduced overhead ratio. It aggregates three important message properties namely number of replicas of a message, its size, and remaining time‐to‐live, using fuzzy logic to determine the message priority, which denotes its importance with respect to other messages stored in a node's buffer. It then intelligently selects messages to schedule when a contact opportunity occurs. Because determination of number of replicas of a message in the network is a difficult task, a new method for estimation of the same has been proposed. Simulation results show improved performance of enhanced fuzzy spray and wait routing in terms of delivery ratio and resource consumption. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : In this work, Spray and Wait routing protocol, which is a popular controlled replication based for delay tolerant networks, has been enhanced using a new fuzzy‐based buffer management strategy (EFSnWR), with the aim to achieve increased delivery ratio and reduced overhead ratio. It aggregates three important message properties, namely number of replicas of a message, its size, remaining time‐to‐live using fuzzy logic controller to determine the message priority.